Insulin resistance, glucagon-like peptide-1 and factors influencing glucose homeostasis in neonates. Issue 2 (2nd September 2016) - Salis, Emma R; Reith, David M; Wheeler, Benjamin J; Broadbent, Roland S; Medlicott, Natalie J
Abstract : Objectives: To explore the relationships between postmenstrual age (PMA), insulin, C-peptide, glucagon and blood glucose concentrations (BGCs) in preterm and term neonates. To compare glucagon-like peptide-1 (GLP-1) concentrations in fed versus never-fed neonates. Design: Observational. Setting: Dunedin Hospital Neonatal Intensive Care Unit, New Zealand. Patients: Term or preterm euglycaemic neonates (102) receiving routine blood tests (343 samples). Interventions: None: plasma was obtained from surplus samples from routine clinical care. Main outcome measures: Insulin, C-peptide, GLP-1 and glucagon concentrations were measured in temporal association with BGC. Results: Insulin and C-peptide concentrations were elevated in very preterm infants (PMA≤32 weeks) and decreased to term; this relationship persisted when BGCs were accounted for. Generalised linear mixed models showed that insulin:C-peptide ratio and insulin:BGC ratio decreased significantly with increasing PMA (p<0.001). GLP-1 increased following initial oral feeds regardless of PMA (p<0.001). Conclusion: Preterm neonates exhibit insulin resistance in the absence of hyperglycaemia. Enteral feeds result in an increase in GLP-1. These factors are likely to contribute to the increased risk of hyperglycaemia in premature neonates (PMA<32 weeks).